2021
DOI: 10.3390/mi12040414
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-BOX SOI: Advanced Silicon Substrate with Pre-Patterned BOX for Monolithic MEMS Fabrication

Abstract: Several Silicon on Insulator (SOI) wafer manufacturers are now offering products with customer-defined cavities etched in the handle wafer, which significantly simplifies the fabrication of MEMS devices such as pressure sensors. This paper presents a novel cavity buried oxide (BOX) SOI substrate (cavity-BOX) that contains a patterned BOX layer. The patterned BOX can form a buried microchannels network, or serve as a stop layer and a buried hard-etch mask, to accurately pattern the device layer while etching it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The fabrication process of the proposed device is similar with the reported paper [21] as this structure is also vertically stack and heterojunction in nature. SOI structure not only provide physical/mechanical strength [24] to the device but also control the leakage or parasitic capacitances [18] and ESD of the device [25].…”
Section: Device Structure and Simulation Parametersmentioning
confidence: 99%
“…The fabrication process of the proposed device is similar with the reported paper [21] as this structure is also vertically stack and heterojunction in nature. SOI structure not only provide physical/mechanical strength [24] to the device but also control the leakage or parasitic capacitances [18] and ESD of the device [25].…”
Section: Device Structure and Simulation Parametersmentioning
confidence: 99%
“…Kluba et al [ 2 ] presented a novel type of substrate for a Silicon on Insulator wafer, which contained a patterned, buried oxide layer that can simplify the fabrication of MEMS devices with complex geometry and added functionality. The authors successfully demonstrated the application of the cavity-BOX SOI substrate in the fabrication of a deep brain stimulation (DBS) demonstrator with a length of 18 mm and a diameter of 1.39 mm.…”
mentioning
confidence: 99%